The Influence of Divalent Anions on the Rectification Properties of Nanofluidic Diodes: Insights from Experiments and Theoretical Simulations - Pérez Mitta, Gonzalo (2016)
During the last decade, the possibility of generating synthetic nanoarchitectures with functionalities comparable to biological entities has sparked the interest of the scientific community related to diverse research fields. In this context, gaining fundamental understanding of the central features that determine the rectifying characteristics of the conical nanopores is of mandatory importance. In this work, we analyze the influence of mono- and divalent salts in the ionic current transported by asymmetric nanopores and focus on the delicate interplay between ion exclusion and charge screening effects that govern the functional response of the nanofluidic device. Experiments were performed using KCl and K₂SO₄ as representative species of singly and doubly charged species. Results showed that higher currents and rectification efficiencies are achieved by doubly charged salts. In order to understand the physicochemical processes underlying these effects simulations using the Poisson-Nernst-Planck formalism were performed. We consider that our theoretical and experimental account of the effect of divalent anions in the functional response of nanofluidic diodes provides further insights into the critical role of electrostatic interactions (ion exclusion versus charge screening effects) in presetting the ionic selectivity to anions as well as the observed rectification properties of these chemical nanodevices.